The ribB FMN riboswitch from Escherichia coli operates at the transcriptional and translational level and regulates riboflavin biosynthesis - Pedrolli, Danielle [UNESP]; Langer, Simone; Hobl, Birgit; Schwarz, Julia; Hashimoto, Masayuki; Mack, Matthias (Wiley, 2015)
FMN riboswitches are genetic elements that, in many bacteria, control genes responsible for biosynthesis and/or transport of riboflavin (vitamin B2 ). We report that the Escherichia coli ribB FMN riboswitch controls expression of the essential gene ribB coding for the riboflavin biosynthetic enzyme 3,4-dihydroxy-2-butanone-4-phosphate synthase (RibB; EC 4.1.99.12). Our data show that the E. coli ribB FMN riboswitch is unusual because it operates at the transcriptional and also at the translational level. Expression of ribB is negatively affected by FMN and by the FMN analog roseoflavin mononucleotide, which is synthesized enzymatically from roseoflavin and ATP. Consequently, in addition to flavoenzymes, the E. coli ribB FMN riboswitch constitutes a target for the antibiotic roseoflavin produced by Streptomyces davawensis.
Keywords: Escherichia coli; Fmn riboswitch; Streptomyces davawensis; Riboflavin biosynthesis; Roseoflavin